2022
DOI: 10.3390/cells11040646
|View full text |Cite
|
Sign up to set email alerts
|

Role of Integrins in Modulating Smooth Muscle Cell Plasticity and Vascular Remodeling: From Expression to Therapeutic Implications

Abstract: Smooth muscle cells (SMCs), present in the media layer of blood vessels, are crucial in maintaining vascular homeostasis. Upon vascular injury, SMCs show a high degree of plasticity, undergo a change from a “contractile” to a “synthetic” phenotype, and play an essential role in the pathophysiology of diseases including atherosclerosis and restenosis. Integrins are cell surface receptors, which are involved in cell-to-cell binding and cell-to-extracellular-matrix interactions. By binding to extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 108 publications
(117 reference statements)
2
15
0
Order By: Relevance
“…14,15 Previous investigators have reported that integrin-induced signaling pathway activation potentially induces SMC proliferation, migration, survival, and phenotype modulation. [16][17][18] Uniquely, SMCs are not terminally differentiated and maintain plasticity to shift from a normal contractile state towards a synthetic proliferative, migratory and proteolytic state, which contributes to aneurysm formation. Performing a proteomic screen during aneurysm formation in the MFS Fbn1 C1039G/+ mouse model, Parker et al 19 reported enhanced integrin β3 protein expression, then illustrated in vitro overexpression in aortic SMCs potentiated noncanonical TGF-β signaling and SMC phenotype switching.…”
mentioning
confidence: 99%
“…14,15 Previous investigators have reported that integrin-induced signaling pathway activation potentially induces SMC proliferation, migration, survival, and phenotype modulation. [16][17][18] Uniquely, SMCs are not terminally differentiated and maintain plasticity to shift from a normal contractile state towards a synthetic proliferative, migratory and proteolytic state, which contributes to aneurysm formation. Performing a proteomic screen during aneurysm formation in the MFS Fbn1 C1039G/+ mouse model, Parker et al 19 reported enhanced integrin β3 protein expression, then illustrated in vitro overexpression in aortic SMCs potentiated noncanonical TGF-β signaling and SMC phenotype switching.…”
mentioning
confidence: 99%
“…The inhibition of the mevalonate pathway (responsible for cholesterol biosynthesis) also inhibits geranylgeranylation and farnesylation, and consequently reduces prenylation of proteins such as RhoA, inhibiting their activity [98] . Fluvastatin blocks lipoprotein(a)-induced RhoA activity in human SMCs, negating the detrimental effects of lipoprotein(a) on vascular remodeling [57] . Similarly, fluvastatin inhibits PDGF-induced proliferation in rodent SMCs via the inhibition of RhoA, preventing transition to a synthetic phenotype and aberrant vascular remodeling [99] .…”
Section: Rhoa and Statinsmentioning
confidence: 96%
“…Integrins are transmembrane receptors, which are responsible for linking the cell cytoskeleton to the extracellular matrix, and this accounts for SMC phenotypic changes [56] . Integrin αVβ3 activates RhoA through the tyrosine kinase pathway to mediate directional migration [57] . This integrin is weakly expressed in contractile SMCs, but is activated in response to vitronectin, osteopontin and fibronectin [58] .…”
Section: Promotion Of the Synthetic (Dedifferentiated) Smc Phenotypementioning
confidence: 99%
“…An important general question concerns the nature of ECM remodeling events within vessel walls that occurs following vascular injury responses arising from different disease states (Figure 1). Vascular ECM remodeling events result from (1) leakage and deposition of plasma ECM components into the vessel wall 62,72,81 ; (2) ECM degradation of basement membranes, elastic lamellae or interstitial collagen matrices by proteinases such as MMPs and elastases 58,82–85 ; (3) synthesis and deposition of injury-induced ECM components including cellular FNs, osteopontin, tenascin C, and proteoglycans 8,34,47,49,65 ; and (4) exposure of matricryptic integrin-binding sites and release of matricryptins. 52,53,56 These matricryptic sites include an abundance of RGD sites from unfolded collagens, 51 FNs including plasma FN 86,87 and an alternatively spliced FN isoform (EDA; also EDGIHEL site), 26,88,89 osteopontin (also SVVYGLR and ELVTDFPTDLPAT sites) 90–93 and tenascin C (also AEIGDIEL) 94 allowing for cell injury responses mediated by αv integrins like αvβ3, αvβ1, 95 and αvβ5 (which bind RGD sites), and α5β1 (which binds the RGD site within FN), as well as α9β1 and α4β1 (which bind the matricryptic peptide sequences in parentheses from cellular FN, osteopontin, or tenascin C).…”
Section: Ecm Alterations In Vascular Disease States and Vascular Cell...mentioning
confidence: 99%